Sizing Geographic of the Shale Gas Supply Chain: A Case of Mexico - Ruvalcaba, Loecelia; Correa, Gabriel; Caballero-Rico, Frida Carmina; FernÃƒÂ¡ndez-Lambert, Gregorio (International Journal of Supply Chain Management, 2017)
With the enactment of energy reform in Mexico, some of the energy sector activities are opened to national and foreign private investment. It is expected that this new panorama generates important changes for this sector and thus produce significant positive effects on the economy, especially if national companies associated with its supply chain manage to insert in the new productive dynamic. To locate this context, this research allowed identifying, typifying and quantifying Mexican companies dedicated to carrying out economic activities associated with the shale gas core business, in order to measure each of the links in its supply chain and identify some of its main strengths and opportunities. The results show that in Mexico exist mainly micro and small enterprises engaged in the production of goods and services for this sector, supported in conventional resources, with low possibility of effective integration into the supply chain competitively in cost and quality, against international companies with experience in conducting this kind of activities.